War culture and the contest of images - Apel, Dora, 1952- (New directions in international studies., 2012)
War Culture and the Contest of Images analyzes the relationships among contemporary war, documentary practices, and democratic ideals. Using carefully chosen case studies, Dora Apel examines a wide variety of images and cultural representations of war in the United States and the Middle East, including photography, performance art, video games, reenactment, and social media images. Simultaneously, she explores the merging of photojournalism and artistic practices, the effects of visual framing, and the construction of both sanctioned and counter-hegemonic narratives in a global contest of imag.